Pré-natal odontológico em um município de grande porte do nordeste brasileiro - Silva, José Saturnino da (2023)
The dental prenatal care (PNO) in the family health strategy (ESF) has as its initial milestone for its institution the guidelines of the national oral health policy published in 2004, which encouraged the expansion of dental services for pregnant women. Prenatal dental care in Brazilian municipalities has faced numerous barriers to its consolidation. The coverage of this service is still considered low, and dentists find it difficult to be included in the teams that provide care to pregnant women, performing the care in isolation, focusing on curative actions. This work aims to know how the dentists of the family health strategy (ESF) of the city of Parnamirim/RN have performed the dental prenatal care. This is a quantitative and descriptive study with a cross-sectional design, carried out with 36 dentists. The data were collected from a semi-structured questionnaire, prepared by the researcher and guided by the current literature, using a Likert scale, with the objective of questioning the dental surgeons about conceptions, behaviors and work processes during the dental prenatal care within the ESF. The Microsoft Excel program was used for tabulation and analysis, with the support of the free software R Studio. It was found that 86% of the participants perform dental care to pregnant women, 39% of them eventually contemplate both individual and collective actions in their practice. For 44% of the interviewees, the educational actions are performed more frequently than the curative actions; 75% do not perform home visits to puerperal women, and 50% do not participate in groups for pregnant women. It is concluded that it is necessary to enhance the use of tools or strategies to increase the adherence of pregnant women to the PNO, there is a need for balance between the actions performed, whether collective, individual, curative or preventive. Practices that mainly involve interprofessional planning and joint actions, such as groups for pregnant women, shared consultations, and puerperal home visits are not consolidated in the routine of the dental surgeons of the municipality’s ESF. The permanent/continuing education involving the theme needs to be included in the professionals’ calendar, however, it has been given little or no value by the management.